2019
DOI: 10.1002/acn3.50925
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic biomarkers of epilepsy development in patients with acute brain injury: a matched, parallel cohort study

Abstract: ObjectiveThis study was designed to investigate if highly epileptic electroencephalogram (EEG) findings in patients with acute brain injury increase the long‐term risk of epilepsy development.MethodsAdults patients, lacking epilepsy history, with electrographic seizures or lateralized periodic discharges (LPDs) (cases) were identified and matched based on age, mental status, and etiology with the ones lacking any epileptiform activity (controls) on continuous EEG (cEEG) during hospitalization. The primary outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…The follow‐up period in our study is too short to draw any conclusion about the safety of ASM discontinuation before hospital discharge. Prior evidence suggests that only 5%–7% of patients with acute brain injury lacking ASySs and EAs on cEEG develop epilepsy 34,36 …”
Section: Discussionmentioning
confidence: 99%
“…The follow‐up period in our study is too short to draw any conclusion about the safety of ASM discontinuation before hospital discharge. Prior evidence suggests that only 5%–7% of patients with acute brain injury lacking ASySs and EAs on cEEG develop epilepsy 34,36 …”
Section: Discussionmentioning
confidence: 99%
“…As the COVID-19 pandemic continues, there is a need to better understand the neurological manifestations and associated complications of COVID-19. Acute, clinical, and non-clinical seizures are well-known complications in critically ill patients with sepsis and brain injury ( Oddo et al, 2009 , Newey et al, 2018 , Punia et al, 2019 ). Continuous electroencephalogram (cEEG) monitoring in acutely ill patients has revealed that the acute seizures these patients face are mostly non-convulsive ( Claassen et al, 2004 , Rodriguez Ruiz et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this activity could not be associated with the development of acute or late seizures (Karhunen et al, 2006). Clinical research already showed the role of epileptiform abnormalities in predicting acute post-stroke seizures (Mecarelli et al, 2011) and more recent research also showed an increased risk of late seizures following early epileptiform abnormalities in patients suffering from acute brain injury (Bentes et al, 2018;Punia et al, 2019;Chen et al, 2021). Furthermore, there is some evidence that post-stroke interictal epileptiform activity is associated with neurological deterioration (Claassen et al, 2007;Scoppettuolo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%